The “ideal” spectrograph for atmospheric observations - Platt, Ulrich; Wagner, Thomas; Kuhn, Jonas; Leisner, Thomas (Atmospheric measurement techniques, 2021)
Abstract. Spectroscopy of scattered sunlight in the near-UV to near-IR spectral ranges has proven to be an extremely useful tool for the analysis of atmospheric trace gas distributions. A central parameter for the achievable sensitivity and spatial resolution of spectroscopic instruments is the étendue (product of aperture angle and entrance area) of the spectrograph, which is at the heart of the instrument. The étendue of an instrument can be enhanced by (1) upscaling all instrument dimensions or (2) by changing the instrument F number, (3) by increasing the entrance area, or (4) by operating many instruments (of identical design) in parallel. The étendue can be enhanced by (in principle) arbitrary factors by options (1) and (4); the effect of options (2) and (3) is limited. We present some new ideas and considerations of how instruments for the spectroscopic determination of atmospheric gases could be optimized using new possibilities in spectrograph design and manufacturing. Particular emphasis is on arrays of massively parallel instruments for observations using scattered sunlight. Such arrays can reduce size and weight of instruments by orders of magnitude while preserving spectral resolution and light throughput. We also discuss the optimal size of individual spectrographs in a spectrograph array and give examples of spectrograph systems for use on a (low Earth orbit) satellite, including one with sub-kilometre ground pixel size.